Biological Nitrogen Fixation on Legume - Armiadi . (Indonesian Center for Animal Research and Development, 2009)
Nitrogen (N) is one of the major limiting factors for crop growth and is required in adequate amount, due to its function as protein and enzyme components. In general, plants need sufficient nitrogen supply at all levels of growth, especially at the beginning of growth phase. Therefore, the availability of less expensive N resources would reduce the production cost. The increasing use of chemical fertilizer would probably disturb soil microorganisms, reduce the physical and chemical characteristics of soil because not all of N based fertilizer applied can be absorbed by the plants. Approximately only 50% can be used by crops, while the rest will be altered by microorganism into unavailable N for crops or else dissappear in the form of gas. Leguminous crops have the capacity to immobilize N2 and convert into the available N if innoculated with Rhizobium. The amount of N2 fixed varies depending on legume species and their environment. Key words: Nitrogen fixation, legume